Pharmacokinetics of quinine and 3-hydroxyquinine in severe falciparum malaria with acute renal failure. - Newton, P; Keeratithakul, D; Teja-Isavadharm, P; Pukrittayakamee, S; Kyle, D; White, N (1999)
The plasma concentrations of quinine and its main metabolite, 3-hydroxyquinine (3OHQn), were measured in 5 adult Thai patients with severe Plasmodium falciparum malaria and acute renal failure. Two patients required peritoneal dialysis but all survived. During acute renal failure plasma concentrations of 3OHQn rose to reach up to 45% of the levels of the parent compound. The estimated median (range) quinine clearance was 0.83 mL/kg/min (0.58-1.16), and 3OHQn clearance/fraction of quinine converted was 3.40 mL/kg/min (2.58-4.47). The estimated 3OHQn terminal elimination half-life was 21 h (16.5-32.5). These data suggest that 3OHQn contributes about 12% of the antimalarial activity of the parent compound in patients with falciparum malaria and acute renal failure. It is also likely that 3OHQn contributes to adverse effects, although this metabolite is not quantitated routinely by current high-performance liquid chromatography quinine assays.